Hot and cold executive functions in youth with psychotic symptoms. Issue 16 (7th June 2017) - MacKenzie, L. E.; Patterson, V. C.; Zwicker, A.; Drobinin, V.; Fisher, H. L.; Abidi, S.; Greve, A. N.; Bagnell, A.; Propper, L.; Alda, M.; Pavlova, B.; Uher, R.
Abstract : Background: Psychotic symptoms are common in children and adolescents and may be early manifestations of liability to severe mental illness (SMI), including schizophrenia. SMI and psychotic symptoms are associated with impairment in executive functions. However, previous studies have not differentiated between 'cold' and 'hot' executive functions. We hypothesized that the propensity for psychotic symptoms is specifically associated with impairment in 'hot' executive functions, such as decision-making in the context of uncertain rewards and losses. Methods: In a cohort of 156 youth (mean age 12.5, range 7–24 years) enriched for familial risk of SMI, we measured cold and hot executive functions with the spatial working memory (SWM) task (total errors) and the Cambridge Gambling Task (decision-making), respectively. We assessed psychotic symptoms using the semi-structured Kiddie Schedule for Affective Disorders and Schizophrenia interview, Structured Interview for Prodromal Syndromes, Funny Feelings, and Schizophrenia Proneness Instrument – Child and Youth version. Results: In total 69 (44.23%) youth reported psychotic symptoms on one or more assessments. Cold executive functioning, indexed with SWM errors, was not significantly related to psychotic symptoms [odds ratio (OR) 1.36, 95% confidence interval (CI) 0.85–2.17, p = 0.204). Poor hot executive functioning, indexed as decision-making score, was associated with psychotic symptoms after adjustment for age, sex and familial clustering (OR 2.37, 95% CI 1.25–4.50, p = 0.008). The association between worse hot executive functions and psychotic symptoms remained significant in sensitivity analyses controlling for general cognitive ability and cold executive functions. Conclusions: Impaired hot executive functions may be an indicator of risk and a target for pre-emptive early interventions in youth.